Research progress and controversies in the treatment of functional constipation-related depression with probiotics and prebiotics: a narrative review - Dai, Qiuhua; Duan, Zhongyu; Fang, Chao; Chen, Rong (Frontiers in Pharmacology, 2026)
Functional constipation (FC) commonly co-occurs with depression, with the microbiota–gut–brain axis providing a biological basis for this association. Designed as a narrative review employing systematic search strategies to ensure comprehensive coverage while accommodating evidence heterogeneity, this study evaluates the efficacy and safety of probiotics, prebiotics, and synbiotics (PP/S) in FC with comorbid depression. Using the terms “probiotic/prebiotic/synbiotic,” “functional constipation,” and “depression” as subject headings and free-text keywords, we analyzed the available evidence. Current evidence suggests that, in adults (including some older adults), PP/S are associated with improvements in spontaneous bowel movements and stool form (Bristol Stool Form Scale), alongside reductions in abdominal symptoms. Regarding psychological outcomes, depressive scores show potential small-to-moderate reductions (most consistently observed within 4–8 weeks); however, high-quality evidence specifically targeting “dual improvement” in patients with co-occurring FC and depression remains preliminary and is often limited by the high placebo response rates characteristic of functional disorders. Overall tolerability is good, with mainly mild gastrointestinal discomfort. Clinically, PP/S may serve as an additional treatment for adults with FC and depressive symptoms, especially when standard approaches are insufficient; however, given that efficacy data are largely extrapolated from primary depression studies and prone to placebo confounding, their use should be guided by the limited certainty of current evidence, given heterogeneity in strains/doses/durations/endpoints and short follow-up. More stratified, multicenter, long-term Randomized Controlled Trials (RCTs) are needed to confirm durability and identify patients most likely to benefit. Given substantial heterogeneity in strains/doses/durations and outcome definitions, we did not perform a quantitative meta-analysis or a de novo risk-of-bias assessment; evidence certainty ratings, where reported, are extracted from prior systematic reviews/meta-analyses.